The effectiveness of psychological treatment in adult male convicted for sexual offenses against children: A systematic review - Sousa, Marta (2022)
Child sexual abuse is a public health problem of global magnitude with profound and negative consequences for the victims and society. Thus, psychological intervention with individuals who sexually offended against children is crucial for reducing recidivism. Numerous reviews and meta-analyses have shown the effectiveness of psychological interventions in individuals who sexually offended, but few reviews have been done on this subtype of offenders. This article reviews evaluation studies of intervention programs designed to treat individuals who sexually offended against children, providing a more detailed account of treatment procedures. Articles were identified from peer-reviewed databases, bibliographies, and experts. Following full-text review, 12 studies were selected for inclusion by meeting the following criteria: quantitative or qualitative research studies published in English from 2000 to 2020 with titles or abstracts that indicated a focus on treatment effectiveness, detailing the psychological treatment procedures on adult, male individuals convicted for child sexual abuse. Cognitive-behavioral therapy with a relapse prevention approach was the most frequent modality found in child sexual offending treatment. Besides, different criminogenic and non-criminogenic factors emerge as targets for intervention. Study design, study quality, and intervention procedures shortened the accumulation of evidence in treatment effectiveness. [ABSTRACT FROM AUTHOR] Copyright of Trauma, Violence & Abuse is the property of Sage Publications Inc. and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract. (Copyright applies to all Abstracts.)